METODE PELAKSANAAN KONSTRUKSI REVETMENT - Wayan Jawat (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2017)
ABSTRACT Construction method is the key to be able to realize the entire planning into a physical building form. Basically the construction method is the application of the concept of engineering based on the relationship between the requirements in the tender documents (procurement documents), technical and economic conditions that exist in the field, and all resources including the experience of contractors. The role of the method of carrying out a construction project work is to construct ways of working in the performance of a job and a means of fulfilling, determining the means of employment that support the implementation of a work such as establishing, selecting the equipment to be used in the work appropriate to the type of work effective and efficient in operating costs. How it works can also help in determining the sequence of work, arrange the schedule so that it can determine the completion of a job. Coastal areas are highly intensive areas for human activities such as: government centers, settlements, industries, ports, fishponds, buffers and tourism. The island of Bali is a major international tourist destination so keeping the beach in good condition is a must. This has made the development of natural land function especially in coastal and coastal areas as the buffer of ecological cycle (Public Works Agency of Bali Province, 2014). The main material in making this revetment is andesite stone consisting of andesite stone weighing 475-525kg, 100 kg, and 10-40 kg, as for the workmanship using the help of heavy equipment in the form of excavators to move construction materials. Keyword: method, construction, revetment, coastal